Bladder Neuromodulation in Acute Spinal Cord Injury via Transcutaneous Tibial Nerve Stimulation: Cystometrogram and Autonomic Nervous System Evidence From a Randomized Control Pilot Trial - Stampas, Argyrios; Gustafson, Kenneth; Korupolu, Radha; Smith, Christopher; Zhu, Liang; Li, Sheng (Frontiers in Neuroscience, 2019)
AIMS: Percutaneous tibial nerve stimulation is used to decrease incontinence in chronic neurogenic bladder. We report the findings from a subset of patients in a randomized control trial of transcutaneous tibial nerve stimulation (TTNS) for bladder neuromodulation in acute spinal cord injury (SCI) in whom heart rate variability (HRV) was recorded before and after cystometrogram (CMG). The aim was to correlate autonomic nervous system (ANS) changes associated with the CMG changes after the trial using HRV analyses. METHODS: The study was a double-blinded sham-controlled 2-week trial with consecutive acute SCI patients admitted for inpatient rehabilitation, randomized to TTNS vs control sham stimulation. Pre- and Post- trial CMG were performed with concurrent 5-minute HRV recordings with empty bladder and during filling. Primary outcomes were changes with CMG between/ within groups and associations to the HRV findings. RESULTS: There were 10 subjects in the TTNS group and 6 in the control group. Pre-trial baseline subject characteristics, blood pressures (BPs), and CMG were similar between groups. In both groups, the pre-trial systolic BP increased during filling CMG. After the trial, the control group had significantly decreased bladder capacity and increased counts of detrusor-sphincter dyssynergia on CMG, not seen in the TTNS group. Also, the control group did not maintain rising BP post-trial, which was observed pre-trial and remained in the TTNS group post-trial. HRV was able to detect a difference in the ANS response to bladder filling between groups. Post-trial HRV was significant for markers of overall increased parasympathetic nervous system activity during filling in the controls, not seen in the TTNS group. CONCLUSIONS: Preliminary evidence suggests that TTNS in acute SCI is able to achieve bladder neuromodulation via modulation of ANS functions.